Development Training of Android-Based Interactive Learning Application as Supporting Media in Online Learning - Ahmad Swandi; Sri Rahmadhanningsih; Nurhayati Nurhayati; Susalti Nur Arsyad; Asdar Asdar; Bunga Dara Amin; Sparisoma Viridi (International Journal of Public Devotion, 2021)
In supporting the success of online learning, it is necessary to increase the creativity of educators in developing and using learning media applications. The purpose of this research is to provide training and assistance to lecturers, teachers and prospective teacher students in making Windows and Android-based learning applications. The structured training program is carried out in collaboration between lecturers from the Teacher Training and Education Faculty and partner teams from the Permata Bunda Educational Institution through the Kedaireka Matching Fund program. The training was carried out in a hybrid manner with details of 10 participants participating offline and 60 participants participating online. The training was carried out for one day by dividing into 3 types of activities, namely the introduction of learning applications, direct practice of making learning applications and as a closing activity a questionnaire was given as an evaluation of the success of the activity. Based on the evaluation results obtained information that 14.26% of participants have been able to develop learning applications up to the publication stage, 71.43% of participants have been able to develop learning application content and 10% of participants are able to complete the learning media framework design stage, while 4 ,26% are still at the stage of program installation. In addition, at the end of the activity, participants also filled out a satisfaction questionnaire with the ongoing training activities. Based on the response analysis of participants' satisfaction above 85% which is included in the very good category. This shows that participants are very satisfied with the training they have received